Perancangan Aplikasi E-Office Berbasis Web - Randa, Gusti Randa; Mulya, Rudi; Limay Trisno Putra, Ari (Fakultas Teknik Universitas Nahdlatul Ulama Sumatera Barat, 2023)
The development of information technology is growing so rapidly, so that many sophisticated telecommunications or communication tools have emerged such as television, cellular, radio, telegram and so on, but there are still written applications that cannot be forgotten until now. This written application is still used as if it cannot be replaced by various sophisticated communication equipment, namely letters. The use of letters is still found in many institutions, but there are still errors in the management process, especially at the Nahdlatul Ulama University, West Sumatra. with the background of the problem, the author will design an E-Office application at the Nahdlatul Ulama University of West Sumatra. The E-Office application is an online correspondence application that aims to help facilitate mail management activities at the Nahdlatul Ulama University of West Sumatra. This digital system is present as a solution to the problems that arise in the correspondence process which is still done manually at the Nahdlatul Ulama University of West Sumatra, so that the correspondence process at the Nahdlatul Ulama University of West Sumatra is still slow in its management. By building an E-Office application at the Nahdlatul Ulama University of West Sumatra, hopefully it can help, speed up and make it easier for the Nahdlatul Ulama University of West Sumatra to process correspondence. In making this E-Office application, the applications used are XAMPP, PHP, Database and other supporting applications.